Elevated fasting insulin is associated with cardiovascular and metabolic risk in women with polycystic ovary syndrome. Issue 3 (May 2019) - Rasool, Shayaq Ul Abeer; Ashraf, Sairish; Nabi, Mudasar; Rashid, Fouzia; Fazili, Khalid Majid; Amin, Shajrul
Abstract: Aims: PCOS is associated with various immediate and long term health complications. The aim of this study was to investigate the association of serum fasting insulin concentration with cardiovascular and metabolic risk factors in women with polycystic ovary syndrome. Methods: A total of 349 women, 249 women with polycystic ovary syndrome and 100 age-matched healthy controls, were recruited in this case-control study. Fasting insulin and various other biochemical, hormonal and clinical parameters were measured in all participants. The correlation of insulin with cardiometabolic risk factors was evaluated in PCOS women with normal and high serum insulin concentration. Results: Fasting Insulin, BMI, WHR, FAI, LH: FSH, HOMA, QUICKI were significantly higher in PCOS women compared with healthy controls (p < 0.01). Fasting insulin showed a positive correlation with more cardiovascular and metabolic risk factors in PCOS compared to controls. The BMI, BAI, LAP, HOMA IR, QUICKI and FAI were significantly higher (all p < 0.05) in PCOS patients with higher insulin levels than with PCOS women with normal levels. Conclusion: Fasting insulin is an important determinant in the pathogenesis of obesity and hyperandrogenism in PCOS. It is associated with an increased risk of cardiovascular and metabolic disorders in women with PCOS.